Creativity and feature writing : how to get hundreds of new ideas every day - Levenson, Ellie (London : Routledge, 2015)
Creativity and Feature Writing explores how to generate ideas in feature writing. Using clear explanations, examples and exercises, experienced feature writer and teacher Ellie Levenson highlights how feature writers, editors and bloggers can generate ideas and how to turn these into published, paid for articles. A variety of approaches to idea generation are explored including getting feature ideas from:objects, your own life and the lives of othersthe news and non-news articles, including books, leaflets, the internet and any other printed matterpress releases, and from direct contact with charities and press officersnew people, new places and new experiences.The book draws on a range of tips from practicing journalists and editors and displays case studies of example features to chart ideas from conception to publication.
Keywords: Feature writing -- Handbooks, manuals, etc; Journalism -- Authorship -- Handbooks, manuals, etc